Guided Inquiry Module Based On Augmented Reality To Improve Cognitive Learning Outcomes And Science Process Skills In Biology Technology Innovation - Askari Eka Yunianto; Evy Yulianti; Ahmad Kamal Sudrajat (Journal of World Science, 2025)
This research aims to develop a guided inquiry-based module integrated with Augmented Reality (AR) to improve cognitive learning outcomes and science process skills of tenth-grade high school students on the topic of biological technology innovation. The study adopts the ADDIE development model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. At the analysis stage, needs assessment was conducted through interviews, observations, and questionnaires to identify learning problems and student difficulties in understanding complex and abstract biotechnology concepts. The design and development stages involved creating an AR-based guided inquiry module that combined interactive visualizations, guided inquiry activities, and Higher Order Thinking Skills (HOTS)-oriented exercises. The product was validated by material experts, media experts, and learning experts to ensure content accuracy, media feasibility, and instructional appropriateness. Implementation was carried out using a quasi-experimental design with control and experimental groups, where pre-tests and post-tests were administered to measure learning gains. The evaluation stage included formative evaluation during development and summative evaluation after implementation. The findings indicate that the AR-based guided inquiry module is feasible, practical, and effective in enhancing students’ cognitive achievement and science process skills, while also fostering higher engagement and motivation in learning biology.